Disciplinary Case Study: The Tromsø Repository of Language and Linguistics (TROLLing) - Conzett, Philipp (2019)
Source at http://doi.org/10.5281/zenodo.2668775. Review available at https://libereurope.eu/blog/2019/05/15/two-new-liber-case-studies-on-research-data-management-support-released/. This disciplinary case study was carried out by LIBER's Research Data Management Working Group and focuses on Research Data Management support for language and linguistics provided by the University Library at UiT The Arctic University of Norway.